Pertumbuhan dan produksi kedelai (Glycine max) pada dosis pupuk organik dan cacing tanah yang berbeda - Aris Wahyu Utomo; Adriani Darmawati; Sutarno Sutarno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The research aimed to find out the effect of the interaction between organic fertilizer and earth worm dosage on plant growth and production of soybean. The research was conducted in greenhouse and Laboratory of Ecology and Plant Production of Faculty of Animal and Agricultural Science Diponegoro University, from March – May 2017. The research was arranged using 4x4 factorial design based on Completely Randomized Design. The data weresubjected to analysisof variance (F-test) and followed by Duncan’s Multiple Range Test at 5%. The first factor was dosage of organic fertilizer at 4 different dosage 0 ton/ha (S0), 5 ton/ha (S1), 10 ton/ha (S2), and 15 ton/ha (S3). The second factor was dosage of earth worm at 4 different levels 0 ton/ha (C0), 0.225 ton/ha (C1), 0.450 ton/ha (C2), and 0.675 ton/ha (C3). The result showed the combination of dosage of organic fertilizer and earth worm had effect to plant growth, number of leaves and number of pods. Keywords: Organic Fertilizer, Earth Worm, Soybean